Urban-rural differences in suicide trends in young adults: England and Wales, 1981-1998 - Middleton, Nicos; Gunnell, David J.; Frankel, Stephen J.; Whitley, Elise; Dorling, Daniel (My University, 2003)
Suicide rates amongst young people, particularly males, have increased in many industrialised countries since the 1960s. There is evidence from some countries that the steepest rises have occurred in rural areas. We have investigated whether similar geographical differences in trends in suicide exist in England and Wales by examining patterns of suicide between 1981 and 1998 in relation to rurality. We used two complementary population-based indices of rurality: (1) population density and (2) population potential (a measure of geographic remoteness from large concentrations of population). We used the electoral ward (n=9264, median population aged 15-44: 1829) as the unit of analysis. To assess whether social and economic factors underlie rural-urban differences in trends we used negative binomial regression models to investigate changes in suicide rates between the years for which detailed national census data were available (1981 and 1991). Over the years studied, the most unfavourable trends in suicide in 15-44-year olds generally occurred in areas remote from the main centres of population; this effect was most marked in 15-24-year-old females. Observed patterns were not explained by changes in age- and sex-specific unemployment, socio-economic deprivation or social fragmentation. The mental health of young adults or other factors influencing suicide risk may have deteriorated more in rural than urban areas in recent years. Explanations for these trends require further investigation.
Keywords: Suicide; Mental health; Social fragmentation; Urban–rural differences; England and Wales